A Millennium Translation Based on the Geʿez and LXX: A New Bible Translation in the Ethiopian Church and Its Controversy - Asale, Bruk Ayele (The Bible translator, 2014)
Being one of the earliest Christian churches, the Ethiopian Orthodox Tewahedo Church (EOTC) collection of Scriptures is the largest, though without a clear-cut canon. Following its unique calendar, the EOTC published its first Amharic Bible ever for the Ethiopian millennium celebration in 2007. It was based on the Geʿez and the LXX versions, which resulted in a strong negative reaction from some believers in the Evangelical churches in Ethiopia. After a brief survey of the translation and transmission history of Scriptures in Ethiopia, the article discusses the process of the millennium translation, the reactions against it, and the outcomes of both the translation and its reactions.